Analysis of financial management of village owned enterprises / Septia Asliyanni … [et al.] - Asliyanni, Septia; Kurnianingsih, Heny; Rangkuti, Lusi; Rahayu, Sri; Suginam, Suginam (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The purpose of this study is that researchers want to find out the implementation of village owned enterprise (BUMDes) financial management in Denai Lama Village, Pantai Labu District, Deli Serdang Regency based on Village Minister Regulation number 3 of 2021. This type of research uses qualitative research methods using a descriptive and study approach. cases obtained from interviews with trusted sources at BUMDes Sastro 3-16. The data analysis method goes through several stages, namely data reduction, data presentation, verification conclusions are drawn. The results of this study are that the financial management carried out by BUMDes is still simple. The Planning Stage is carried out by holding deliberations for each unit to form a Draft Budget. The implementation phase is carried out using receipts as proof of disbursement of funds. The Administration stage is carried out by recording cash inflows and disbursements.